Selective CO oxidation in the hydrogen stream over Ru/Al@Al2O3 catalysts - Rah, Il Ji; Kim, Tae Wook; Kim, Jieun; Lee, Doohwan; Park, Eun Duck (Catalysis Today, 2020)
The Al@γ-Al2O3 core-shell microstructures prepared from aluminum particles by hydrothermal surface oxidation were superior to the conventional alumina support owing to the facile heat flux through the metal-ceramic composite structures. The Ru catalysts supported on Al@γ-Al2O3 were used for the preferential CO oxidation (PROX) reaction, which is a highly exothermic reaction requiring high heat flux. For comparison, commercially available α-Al2O3 and γ-Al2O3 were also used as catalyst supports. The catalysts were characterized by N2-physisorption, X-ray diffraction, CO chemisorption, transmission electron microscopy (TEM), temperature-programmed desorption of ethanol (ethanol-TPD) and ammonia (NH3-TPD), and temperature-programmed oxidation (TPO). The Ru/α-Al2O3 catalyst with the lowest Ru dispersion showed the best PROX performance among the tested catalysts in the absence of CO2 and H2O. Even though Ru/Al@γ-Al2O3 and Ru/γ-Al2O3 had similar Ru dispersions, the former catalyst exhibited a much better PROX performance than the latter. This could be explained by the fact that the Ru metal deposited on Al@γ-Al2O3 was more resistant to surface oxidation as compared to that on γ-Al2O3, based on the TPO results. A lower desorption temperature of ethanol was observed over Al@γ-Al2O3 than over γ-Al2O3 during ethanol-TPD experiments, even though both supports had similar amounts of acid sites, as determined by NH3-TPD. Among the tested catalysts, Ru/Al@γ-Al2O3 also showed the best PROX performance in the presence of CO2 and H2O. A further enhancement in the PROX performance was achieved by increasing the Ru metal particle size from 1.4 to 2.6 nm by pretreating the Ru/Al@γ-Al2O3 catalyst with 1 mol% O2 in He at 150 ℃.
Keywords: Aluminum particle; Desorption temperatures; Metal-ceramic composites; N2 physisorption; Preferential CO oxidation; Selective CO oxidation; Surface oxidations; Temperature programmed oxidation; Al@γ-Al2O3; Metal-ceramic composite; Preferential CO oxidation; Ru; Ru/alumina